The influence of profitability, solvency, and company size on audit delay in property and real estate sector companies in 2020-2022 - Rahela Monarissa Br Hutasoit; Zaenal Wafa (Institute of Computer Science (IOCS), 2023)
Audit delay as the time span for completing the annual financial report audit report is measured based on the number of days needed to obtain the independent auditor's financial report for the audit of the financial report. The aim of this research is to determine the effect of profitability, solvency and company size on audit delay in property and real estate sector companies in 2020-2022. This research uses a descriptive method using secondary data in the form of audited financial statements originating from companies listed on the Indonesia Stock Exchange which can be obtained from the website www.idx.co. The results of the profitability research obtained a significance value of 0.307 > 0.05, meaning that H1 was rejected. Solvency has a significance value of 0.418 > 0.05, meaning that solvency has no effect on audit delay. Company size obtains a significance value of 0.046 <0.05, so H1 is accepted.